A Portrait of Spiritlessness in the Age of Leveling - Parding, Mathias G. (Kierkegaard studies. Yearbook, 2018)
Since the spirit of the time greatly influences the individual, Kierkegaard becomes increasingly aware of a socio-political environment in which a specific psychological character is molded, namely that of spiritlessness. Consequently, my primary objective in this paper will be to examine how this character manifests itself as a socio-psychological phenomenon in the age of leveling. How does spiritlessness constitute what we can call a pathology of normality as an emblematic despair of the age? In trying to answer this question I hope to clarify the reason for Kierkegaard's increasingly problematic relation to his time. Since the intimate relationship between the concept of spiritlessness and leveling is given the most systematic account in Two Ages, most of the contributions in this paper will derive from this work.